Transparency and Accountability of Fund Management in Makassar Street Children Community: Netnographic Study - Elly Haerunnisa; Waode Rayyani (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze transparency and accountability practices in managing donation funds at the Makassar Street Children Care Community Komunitas Peduli Anak Jalanan (KPAJ) through social media and their role in building public trust.Methodology: This study employed a qualitative approach with netnography. Data were obtained through observations of KPAJ Makassar's social media activities, documentation of digital uploads, and interviews with community administrators. Data analysis was conducted descriptively through data reduction, data presentation, and drawing conclusions.Results: The findings indicate that Makassar KPAJ has implemented transparency and accountability through the publication of activities, fund utilization reports, and aid distribution on social media. However, these practices remain limited by the absence of a standardized financial reporting system.Conclusions: Transparency and accountability in KPAJ Makassar's fund management have been implemented through social media. However, improvements in financial reporting are needed to strengthen public trust and organizational governance. Limitations: This study only focuses on KPAJ Makassar and is limited to social media data and information from informants, so the results cannot be generalized.Contribution: This research contributes to public sector accounting by promoting transparency, accountability, and improved reporting practices in social media-based fund management.